Determination of the absolute configuration of the novel anti-trypanosomal iridoid molucidin isolated fromMorinda lucida by X-ray analysis - Nguyen, Huu Tung (Tetrahedron Letters, 2016)
The strong anti-trypanosomal active compound, molucidin, contains a spirolactone tetracyclic iridoid skeleton and is isolated fromMorinda lucidaas an enantiomer of oruwacin, which is isolated from the same plant. To confirm the absolute configuration of molucidin, we prepared single crystals of molucidin for X-ray analysis. The absolute configuration of the afforded single crystal was determined by X-ray crystallography using a Cu radiation source. X-ray diffraction data were collected at 93 K in the 2hrange 7.468–134.99 and analyzed using the SHELXL-2014 program. The corresponding chiral quaternary carbon atoms in molucidin were unambiguously determined as 1R,5S,8S,9S, and 10S. Notably, both enantiomers of a single molecule, molucidin and oruwacin, with a rigid structure have been isolated from the same plant species. The biosynthetic pathway for the formation of molucidin is also discussed on the basis of the absolute configuration. Our results for the first time support for structural elucidation of tetracyclic iridoids using X-ray analysis